Criticizing the critics of monetarism (2007)
By the start of the twenty-first century monetarism – unlike a surprisingly adaptable Keynesianism – was being referred to in the past tense. For some people it was a convenient swearword, used to express their loathing for everything that had gone wrong (as they saw it) since conservative governments in the USA and the UK embraced free-market economics in the 1980s. A more sympathetic author interpreted the rise and fall of monetarism in Britain as a problem in ‘social learning’. In his words, writing in the mid-1990s, The social learning process since 1979 has been a mixed affair. The 1980s were a time of policy experiments . . . While it would be wrong to see policy as an unqualified success in the 1980s, it would be equally incorrect to conclude that nothing positive has come from the past 16 years